Motif Batik Kasih Sayang Ibu untuk memaknai Hari Ibu - Fegelia Rahmadani (SULUH: Jurnal Seni Desain Budaya, 2018)
Observed the "Mother's Day" memorial event, which falls on December 22 as National Mother's Day in the country of Indonesia. Today, the meaning of mom's Moment and its essence has changed and shifted. Where Mother's Day commemoration is now only on ceremonial and temporal matters, such as congratulations by social media. Meaning Mother's Day by giving affection, is a beautiful expression. All humans and living beings in this world need love, not exception. Mother's love for her child will not be the same as the child's love for her mother. Like the proverb "mother's love along the way, child love along the pole" from the meaning of the word used is "road and" pole ", the path is connected with another way so that no end. While the pole is a stick that has a certain size that can be seen end and base. With this pattern batik, want to convey feelings of affection for mother as a form of appreciation for his services